SCALING UP EARLY READING INTERVENTION: A STUDY OF THE FUNCTIONING OF LIBRARIES AND AVAILABILITY OF AGE-APPROPRIATE CHILDREN'S LITERATURE - Maria Fatima Mardina Angkur (International Journal of Teaching and Learning, 2025)
This study aims to examine in-depth the role and effectiveness of libraries in supporting early reading interventions through the provision of age-appropriate children's literature. This study used a literature review method, exploring various previous studies, policy reports, and implementation studies focused on early literacy, access to children's reading materials, and the role of educational institutions and community libraries in fostering early reading habits. The analysis shows that the availability of children's books appropriate to children's cognitive and language development levels is strongly correlated with improved early reading skills. Furthermore, library functioning, in terms of collection management, literacy activities, community involvement, and policy support, is a crucial factor in expanding the impact of early literacy programs across various social contexts. However, challenges such as limited resources, lack of training for children's librarians, and a lack of supporting policies remain major obstacles to program scalability. This study concludes that to broadly increase the effectiveness of early reading interventions, an integrated approach is needed to ensure the provision of appropriate children's literature, strengthen library capacity, and collaborate multisectorally between the government, educational institutions, and the community.